CGIAR Initiatives Inception Workshop Report: Inception Workshop of CGIAR Initiatives on Climate Change, Climate Resilience, and Gender Equality, Nandi County, Kenya, 29 November 2022 - CGIAR Initiative on Livestock and Climate; CGIAR Initiative on Low-Emission Food Systems; CGIAR Initiative on Gender Equality (CGIAR System Organization, 2022)
Inception workshop was held on the 29th of November in Kapsabet town to mark the official launch of the three CGIAR initiatives in Nandi County. The workshop intended to build an understanding of CGIAR initiatives in Nandi County and to identify important areas of collaboration with county government, farmer organizations, and private actors in building adaptation and resilience of agri- food systems to climate change. The workshop deliberated on creation of living and learning labs that would enhance uptake of innovations that positively impact agrifood systems, reduce greenhouse gas emissions, empower and enhance women resilience to climate change, and contribute to county government development agenda. Furthermore, the Livestock and Climate initiative explained about their approach to scaling from the farm in collaboration with adaptation pioneers using the theory of positive deviance.